On the enigmatic Heterostomus curvipalpis Bigot, 1857, with a description of the pupa (Diptera, Brachycera) - Coscarón, Sixto; Coscarón, María Del Carmen; Gil-Azevedo, Leonardo H. (Zootaxa, 2013)
The previously unknown pupa of Heterostomus curvipalpis Bigot is described. The morphology of the pupa of Heterostomus is compared with the pupae of Xylophagomorpha, Tabanomorpha and Stratiomyomorpha families, based on five characters, and its phylogenetic position is discussed. Currently placed in Xylophagidae, we conclude that the pupa of Heterostomus shares most characters with the pupae of Pelecorhynchidae.